1978
DOI: 10.2307/2398860
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Flora of Mediterranean and Saharan Africa

Abstract: After defining the state of knowledge and reviewing national inventories, the author looks at the reasons whieh led him to study Mediterranean and Saharan Africa and to detail their biogeographical significance.For Mediterranean and Saharan Africa, the generic and specific richness, the richness of endemics, and the entire biogeographical range are first analyzed at the family level. In the second part, the various biogeographical elements which play a part in the formation of the floras at the generic and spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
200
0
10

Year Published

1994
1994
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(232 citation statements)
references
References 1 publication
22
200
0
10
Order By: Relevance
“…The number of species present in this area is particularly limited (Quézel, 1965), but the ratio of endemic species is relatively high in mountains that act as refugia for plants and animals due to higher rainfall in altitude. The Saharan flora has affinities with those from adjacent regions, mainly with the Mediterranean Basin, Arabia, Sahelian and Tropical Africa (Quézel, 1978(Quézel, , 1997. Genetic studies have confirmed that some Saharan species are closely related to Mediterranean taxa (for example, Senecio, Coleman et al, 2003;Atriplex, Ortíz-Dorba et al, 2005;Erica, McGuire and Kron, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of species present in this area is particularly limited (Quézel, 1965), but the ratio of endemic species is relatively high in mountains that act as refugia for plants and animals due to higher rainfall in altitude. The Saharan flora has affinities with those from adjacent regions, mainly with the Mediterranean Basin, Arabia, Sahelian and Tropical Africa (Quézel, 1978(Quézel, , 1997. Genetic studies have confirmed that some Saharan species are closely related to Mediterranean taxa (for example, Senecio, Coleman et al, 2003;Atriplex, Ortíz-Dorba et al, 2005;Erica, McGuire and Kron, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The populations of O. e. laperrinei have regressed with the desert expansion during the Pleistocene (Wickens, 1976;Quézel, 1978;Maley, 1980). Small populations are present in mountains from central Sahara (Algeria: Hoggar, Tassili n'Ajjer, Mouydir; and Niger: Greboun, Tamgak, Bagzane) to northeast Sudan (Jebel Marra, Gourgueil).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we can suppose that the subgenus Olea originated in Africa rather in Asia where it is also present. Quezel ( 1978) and Maley ( 1980) have already suggested an African origin for 0. europaea species in the Rand-Flora (indigenous African flora adapted to Mediterranean climate). Consequently, the section Olea and the section Ligustroides probably originated from the Rand-Flora about I 0 to 20 millions years ago.…”
Section: Origin Of the Genus Oleamentioning
confidence: 96%
“…La persistenza nei secoli di diverse forme di eccessivo sfruttamento da parte dell'uomo ha causato la notevole riduzione di buona parte dei tipi forestali climax della regione mediterranea (Quézel 1978). Le rimanenti foreste sono boschi alterati in modo più o meno intensivo da parte dell'uomo che spesso corrispondono a diversi stadi di successione regressiva della foresta originaria.…”
Section: Le Formazioni Forestali Del Mediterraneounclassified